Hubungan Status Gizi Ibu Hamil dengan Berat Badan Lahir di BPM Bidan Sri Harti: Relationship between Nutritional Status of Pregnant Women and Birth Weight at BPM Midwife Sri Harti - Yulia Nur Khayati; Anggraini Khoirum Ningdiah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Ngudi Waluyo, 2023)
In Indonesia, the Infant Mortality Rate in 2021 is 20.1/1000 live births, although this rate is much better and decreased compared to 2020 of 28.1/1000 live births.. In Semarang Regency the incidence of low birth weight is 5.2/1000 live births which is still a concern of the government in efforts to reduce low birth weight. One of the factors that affect birth weight is the nutritional status of pregnant women. Purpose: This study aims to determine the relationship between nutritional status and birth weight. This research is a correlation study with a cross-sectional design. This research was conducted in September 2022 - January 2023 at BPM Bidan Sri Harti. The population of this study were all newborns born at BPM Bidan Sri Harti in 2022 totaling 162 respondents. The sample in this study using total sampling. Data collection techniques use secondary data compiled using a master table. This study was analyzed bivariately using the Chi Square test. There is a significant relationship between the nutritional status of pregnant women and birth weight, with a p-value of 0.000 (<0.05), and OR 29.760. There is a relationship between the nutritional status of pregnant women and birth weight. Planning for pregnancy preparation in pregnant women by taking into account the nutritional status of the mother in order to prevent the occurrence of abnormal birth weight. ABSTRAK Di Negara Indonesia jumlah AKB tahun 2021 sebesar 20,1/1000 kelahiran hidup meskipun angka ini jauh lebih baik dan menurun dibanding tahun 2020 sebanyak 28,1/1000 kelahiran hidup. Pada Kabupaten Semarang kejadian BBLR sebanyak 5,2/1000 kelahiran hidup dimana masih menjadi perhatian pemerintah dalam upaya penurunan BBLR. Salah satau faktor yang mempengaruhi berat badan lahir adalah status gizi ibu hamil. Penelitian ini bertujuan mengetahui hubungan status gizi dengan berat badan lahir. Penelitian ini adalah penelitian korelasi dengan desain cross sectional. Penelitian ini dilaksanakan pada September 2022 – Januari 2023 di BPM Bidan Sri Harti. Populasi penelitian ini adalah seluruh bayi baru lahir yang lahir di BPM Bidan Sri Harti pada tahun 2022 berjumlah 162 responden. Sampel dalam penelitian ini dengan menggunakan total sampling. Teknik pengumpulan data menggunakan data sekunder yang disusun menggunakan master tabel. Penelitian ini dianalisis bivariat menggunakan uji Chi Square. Terdapat hubungan yang signifikan antara status gizi ibu hamil dengan berat badan lahir, dengan hasil p-value 0,000 (< 0,05), dan OR 29,760. Terdapat hubungan status gizi ibu hamil dengan berat badan lahir. Perencanaan persiapan kehamilan pada ibu hamil dengan memperhatikan status gizi ibu agar mencegah kejadian berat badan lahir tidak normal.